The analysis of adaptation process of students to teaching in higher education institution with use of means of physical education - Sergei Horodynskyi; Igor Havrunyak (Kharkiv State Academy of Physical Culture, 2017)
Purpose: the analysis of process of adaptation of students of higher education institutions to conditions of teaching and the search of ways of its increase of physical culture and sport. Material & Methods: the detection of features of the period of adaptation of students to the educational process was carried out by the method of the analysis of researches, publications and questioning on the subject of adaptation processes at students of higher education institutions. The attention to features of application of means of physical culture and their positive influence on intellectual and physical data of youth is focused. Results: the detailed consideration of all aspects of process of adaptation to teaching found as negative sides of the process (health aggravation of symptoms, psychological discomfort), and positive (high rates in study, all-round development). Conclusions: the means of physical culture which are skillfully selected and correctly used on classes by the teacher will give the chance to the student to get desirable education with comfort.